Strengthening Literacy Management Among Pesantren-Based Madrasah Teachers Through The Gerakan Satu Madrasah Satu Buku Programme - Ahmad Ihwanul Muttaqin; Atmari Atmari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Syarifuddin Lumajang, 2026)
This study addresses Indonesia’s critically low literacy, evidenced by PISA scores below OECD averages and a reading culture index of 0.001. It examines the Gerakan Satu Madrasah Satu Buku or “One Madrasah One Book Movement” (GSM SAKU) in Lumajang Regency as a participatory intervention to strengthen literacy management among pesantren-based madrasah teachers. Employing Participatory Action Research (PAR), the program engaged 254 participants, including teachers and administrators, in a structured cycle of collaborative planning, book writing, intensive mentoring, and reflection, supported by a multi-stakeholder network. The intervention successfully positioned teachers as knowledge producers, resulting in published books documenting pedagogical practices and transitioning literacy activities from ad hoc to managed institutional programs. Outcomes included enhanced teacher professional confidence, the formation of school literacy teams, and strengthened collaborative networks. The study concludes that a systematic, PAR-based model supported by institutional collaboration can effectively transform literacy management. It provides a replicable framework for improving Islamic education quality and contributes to discourse on knowledge management and teacher professional development in religious educational contexts.